2015
DOI: 10.1002/ghg.1543
|View full text |Cite
|
Sign up to set email alerts
|

The syringe sampler: An inexpensive alternative borehole sampling technique for CO2-rich fluids during mineral carbon storage

Abstract: Mineral carbon storage involves the dissolution of injected gaseous or supercritical CO2 followed by interaction of the carbonated solution with the host rock at depth resulting in the precipitation of carbonate minerals. Monitoring of elemental chemistry and tracers is required to evaluate the evolution of the fluid geochemistry and the degree of CO2 mineralization during its injection into the subsurface. To avoid degassing during sampling, which is a common feature of commercial groundwater samplers, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The dissolved inorganic carbon (DIC) concentration and pH of the injectates were 0.82 mol/liter and 3.85 (at 20°C) for phase I and 0.43 mol/liter and 4.03 for phase II. Fluid samples for SF 6 , SF 5 CF 3 , 14 C, DIC, and pH analyses were collected without degassing using a specially designed downhole sampler from the injection well HN02 (22) or with a submersible pump from the first monitoring well, HN04, located about 70 m downstream from HN02 at 400 m depth below the surface before, during, and after injection (tables S1 to S3).…”
mentioning
confidence: 99%
“…The dissolved inorganic carbon (DIC) concentration and pH of the injectates were 0.82 mol/liter and 3.85 (at 20°C) for phase I and 0.43 mol/liter and 4.03 for phase II. Fluid samples for SF 6 , SF 5 CF 3 , 14 C, DIC, and pH analyses were collected without degassing using a specially designed downhole sampler from the injection well HN02 (22) or with a submersible pump from the first monitoring well, HN04, located about 70 m downstream from HN02 at 400 m depth below the surface before, during, and after injection (tables S1 to S3).…”
mentioning
confidence: 99%
“…To focus and to accelerate the subsurface flow of the gas-charged water into the monitoring wells, about 1 kg s −1 of fluid was pumped out of well HN-04 and about 1 kg s −1 from well HK-34 during and after the injection. Verification of the complete dissolution of CO 2 during its injection was done using a digital downhole camera and by high pressure well water bailer sampler (Alfredsson et al, 2015;Sigfusson et al, 2015). Digital images and videos were taken using a slimline water well inspection camera on 16 March 2011 at depths from 90 to 550 m. The camera and the high pressure bailer travelled within the service pipe (number 7 in Fig.…”
Section: The Carbfix1 Injection Wellmentioning
confidence: 99%
“…The reaction rate of aqueous processes is fast because the alkaline components are present as reactive ions in the aqueous solution. Most of the studies reported in the literature are based on aqueous processes . For example, with the aim of improving efficiency, Huijgen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Mineral carbonation can be divided into dry (gas-solid) and aqueous (gas-liquid or gas-liquid-solid) processes according to the phase in which the carbonation occurs. [11][12][13] The reaction rate of aqueous processes is fast because the alkaline components are present as reactive ions in the aqueous solution. Most of the studies reported in the literature are based on aqueous processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation